A review on recent advancements in wearable microbial fuel cells - Abbas S.Z.; Beddu S.; Kamal N.L.M.; Rafatullah M.; Mohamad D. (Elsevier Ltd, 2025)
The fast proliferation of wearable electronics has ushered in a new era of technological convergence with daily living, necessitating sustainable power solutions. Wearable microbial fuel cells (MFCs), which use microbe's ability to produce energy, have emerged as an innovative solution to this demand. Recent advances in electrode materials, including as conductive polymers, graphene, and carbon nanotubes, are the focus of this overview on wearable MFCs. Hybrid systems, which combine wearable MFCs with technologies like piezoelectric generators, offer comprehensive energy solutions; miniaturization techniques allow for smooth integration into clothing, accessories, and implants. Despite advancements, difficulties in scaling and electrode stability exist, necessitating focused approaches. This review article focuses on how wearable MFCs are changing the energy landscape and ushering in a new era of inventive electronics by advancing sustainable energy and environmental sensing. ? 2024 Elsevier Ltd